Developmental Coordination Disorder, Historical Beginnings and Development - Laganovska, Egija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This article contains theoretical analysis about Developmental Coordination Disorder historical evolution. Studies include a wide variation in terminology and criteria to describe . Developmental Coordination Disorder. Developmental Coordination Disorder is a complex neurological condition, which affects muscle coordination and perception.